The perspective of cooperation between foster parents and the school social workers in elementary schools - Faltová, Barbora; Mojžíšová, Adéla; Holá, Jana (My University, 2024)
Goal: This study aims to discover the interest of foster parents in cooperating with the school social workers in elementary schools to support the children’s school success during foster care. Methods: The quantitative survey was based on a non-standardised questionnaire validated for comprehensibility and relevance by professionals in non-profit organisations who conducted a pilot survey with cooperating foster parents. The research group was created by purposive sampling (n = 102). Descriptive statistics and exploratory analysis methods were used to evaluate the obtained data. Results: Foster parents are provided with expert advice by a non-profit organisation supporting foster families in social services, child rearing, education, and health. In schools, they use the entire spectrum of consulting services of pedagogical staff. They are somewhat satisfied with the support services provided, but show an interest in working with the school social worker to support the children’s school success, health, and well-being. Conclusion: The need to institutionalise the profession of a school social worker in a Czech primary school appears to be a desirable prospective support of a child’s school success and healthy growth, and a necessary help for parents regarding health and social counselling and services, especially when dealing with challenging life situations associated with school attendance. The social worker’s global role has already been institutionalised in many countries around the world.
Perspektiva spolupráce pěstounů a školních sociálních pracovníků na základních školách
Keywords: Child in foster care; Foster care; School social worker; School success; Dítě v pěstounské péči; Pěstounská péče; Školní sociální pracovník; Školní úspěch